Social Interaction and Cultural Adaptation in the Utilization River Water - Qolbiana, Syifa Nur; Harjanti, Diah Trismi; Christanto, Ludovicus Manditya Hari (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study explores the social interactions and cultural adaptation strategies of the Kampung Beting community in utilizing the Kapuas River water for daily life. Despite environmental challenges and water quality issues, the river remains a central element in the community"™s socio-cultural structure. Using a descriptive qualitative method supported by in-depth interviews and direct observation, the study reveals that the Kapuas River water continues to be the primary source for bathing, washing, and sanitation (MCK) due to limited access to clean water infrastructure. The research highlights how traditional practices, local wisdom, and mutual cooperation help the community adapt to environmental limitations. Community members engage in various coping strategies, including filtering water with pumps or alum, collecting rainwater, and purchasing bottled water. Social interactions within the community are shaped by their shared dependence on the river and collective efforts to manage pollution and improve water quality. These findings emphasize the importance of integrating cultural values and social dynamics into sustainable water management strategies and offer valuable insights for policymakers aiming to improve the quality of life in river-based settlements.